Development system for FPGA-based digital circuits - Sklyarov, V. (2011)
“Copyright © [1999] IEEE. Reprinted from 7th Annual IEEE Symposium on Field-Programmable Custom Computing Machines ISBN:0-7695-0375-6. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”